MINAT MELANJUTKAN STUDI PERGURUAN TINGGI SISWA SMKN KOTA SEMARANG - Khasan Setiaji; Desy Rachmawati (Jurnal Pendidikan Ekonomi, 2017)
The existing data shows that the average number of the graduates of SMK Negeri in Semarang City who continued their study to universities was as many as 16.5%. It shows that the graduates' interest in continuing study to universities has not achieved the Minimum Service Standards (SPM) of SMK which states that among 20% of SMK graduates should continue their study to accredited universities. By this finding, this study was aimed at knowing the influence of the socio-economic background and students' self-potential towards the interest of continuing study to universities in the Eleventh graders of SMK Negeri in Semarang City either simultaneously or partially.The population in this study were the Eleventh graders of SMK Negeri in Semarang City, namely 5,067 students. They were sampled into 100 students by using Slovin formulae. Moreover, the sample was divided through proportional cluster sampling, while their data were collected by using questionnaire and documentation. The collected data were analyzed by using descriptive analysis and multiple regression analysis. The results showed that there was a simultaneous influence ofsocio-economic background and self-potential towards the interest in continuing study to universities showed by the significance value of 0.000 < 0.05 and Adjusted R Square of 0.407 (40.7%). Partially, the influence of socio-economic background contributed to the significance value of 0.025< 0.05 and r square as many as 0.226 (22.6%), self-potential influenced the significance value of 0.000 < 0.05 and r square of 0.509 (50.9%) towards the interest in continuing study to universities. DOI: https://dx.doi.org/10.17977/UM014v10i12017p052